Effect of Different Residue Management Practices of Rice on Growth and Yield of Wheat and Soil Health in Rice-Wheat System - Ali, Md. Naiyar; Alam, Md. Parwaiz; Ahmad, Ekhlaque; Sah, Akhilesh (International Journal of Bio-resource and Stress Management, 2016)
The present experiment was conducted in rice-wheat sequence during 2007−08 and 2008−09 in Birsa Agricultural University Farm, Kanke, Ranchi to assess the effect of rice residue management on growth, yield attributes and yield of grain and straw of wheat and soil health. The trial was laid out in randomized block design with three replications having nine treatment combinations. The various rice residue and nitrogen management systems significantly affect the plant height and number effective spike m-2, number of grain ear head-1 were maximum with rice residue incorporation or rice residue retention 25% additional N+recommended NPK over sowing of wheat without incorporation of rice residue and recommended NPK and rice residue incorporation+recommended NPK at wheat sowing during both the years. Among the yield attributes and yield viz. number of effective tillers m-2, length of ear head, and number of grains ear head-1, grain and straw yield were also recorded maximum with the same treatment. Nitrogen uptake by grain and straw influenced significantly by rice residue and nutrient management practices during both the years. Highest nitrogen uptake by grain and straw was recorded under the treatment when rice residue incorporated with 25% additional N+recommended NPK against sowing of wheat without incorporation of rice residue+recommended NPK and rice residue incorporation+recommended NPK.